The treaty, protocols, conventions and supplementary acts of the Economic Community Of West Africa States (ECOWAS) [1975 - 2010]. (Abuja, Nigeria : Federal Ministry of Foreign Affairs, 2011)
A compilation of the teaty, protocols and conventions of the Economic Community Of West Africa States (ECOWAS) from !975 to 2010. It is an update on the first edition witth the addition of 41 Supplementary Acts that emanated in the organization after the first edition.
oif 04/12/14
Ref.
Keywords: Economic Community of West African States; Law and legislation -- Economic Community of West African States; Economic Community of West African States -- Foreign relations; Africa, West -- Economic integration